2020
DOI: 10.1021/acs.jpcb.0c06658
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up View of the Mechanism of Action of Protein-Stabilizing Osmolytes

Abstract: The molecular mechanism of osmolytes on the stabilization of native states of protein is still controversial irrespective of extensive studies over several decades. Recent investigations in terms of experiments and molecular dynamics simulations challenge the popular osmophobic model explaining the mechanistic action of protein-stabilizing osmolytes. The current Perspective presents an updated view on the mechanistic action of osmolytes in light of resurgence of interesting experiments and computer simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…This is probably the reason why such studies shifted to protein stability in osmolytes, in which protein structure remains almost unaltered. The mechanism of protein–osmolyte interaction is far more studied and understood and is often explained in terms of changes in the water structure and dynamics; more precisely by a change in preferential hydration. Generally, the osmolytes are stabilizing (like sucrose and trehalose) and are preferentially accumulated at the protein solvent interface (i.e., water is preferentially included). This theory turns out to be successful in explaining protein stabilization by adding solute almost accurately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably the reason why such studies shifted to protein stability in osmolytes, in which protein structure remains almost unaltered. The mechanism of protein–osmolyte interaction is far more studied and understood and is often explained in terms of changes in the water structure and dynamics; more precisely by a change in preferential hydration. Generally, the osmolytes are stabilizing (like sucrose and trehalose) and are preferentially accumulated at the protein solvent interface (i.e., water is preferentially included). This theory turns out to be successful in explaining protein stabilization by adding solute almost accurately.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the osmolytes are stabilizing (like sucrose and trehalose) and are preferentially accumulated at the protein solvent interface (i.e., water is preferentially included). This theory turns out to be successful in explaining protein stabilization by adding solute almost accurately. Despite a vast number of theoretical and simulation studies, only a few recent experimental papers have hinted at the importance of solvation in osmolyte-induced protein stabilization. Havenith and co-workers studied water dynamics (using terahertz spectroscopy) in the presence of mono- and disaccharides. They found that disaccharides slow down the water dynamics to a greater extent than monosaccharides .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment is naturally crowded by the cellular components, several other cosolvents, salts, etc. Cosolvents, like small sugars, polyols, alcohols, urea, etc., while present along with water, regulate the structural stability and function of proteins by altering equilibria and kinetics of the process by interacting with the proteins either weakly or strongly compared to water. Majorly, two different classes of cosolvents, known as osmolytes (stabilizer) and denaturants, exist.…”
Section: Introductionmentioning
confidence: 99%
“…Based also on artificial crowders, it was furthermore analyzed how crowding effects on the structure of actin may lead to increased stiffness when forming filaments . Closely related are studies of peptides and proteins in the presence of different osmolytes such as TMAO, trehalose, ethylene glycol, and ethanol, as they capture different aspects of the stabilizing and destabilizing molecules that may be encountered in cellular environments. Equally relevant are a number of mostly simulation studies that explore peptide and protein conformations in the presence of ionic liquids, an area of increased interest in itself, as the organic ions present in these solvents also have parallels in biological environments.…”
mentioning
confidence: 99%